Performance of 4KWp Grid-Connected Photovoltaic (GCPV) system using micro-inverter technology for residential application / Nazreen Baharuddin, Sulaiman Shaari and Nurmalessa Muhammad - Baharuddin, Nazreen; Shaari, Sulaiman; Muhammad, Nurmalessa (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Even though the cost of a grid-connected photovoltaic (GCPV) system has decreased significantly as a result of widespread commercial acceptance, current technologies are continually improved to reduce cost and increase efficiency. By contrast, relatively recent technologies such as maximizers and micro-inverters seek to encourage new techniques of solar energy production at a reasonable cost. While micro-inverters are gaining popularity in the solar industry, industry claims of improved system performance remain unproven. Third-party validation is critical for assessing the efficiency of micro-inverter technology. The objective of this research is to analyze the service provider's reported yearly availability performance for a 4kWp residential grid-connected photovoltaic (GCPV) system with micro-inverter technology located in Shah Alam, Malaysia, as well as gauging the owner's satisfaction with the system. The actual data for the years 2017, 2019, and 2020 were analyzed to determine the annual specific yield (SYmea) and performance ratio (PRmea). The results show that the actual annual SYmea varies between 1,144 kWh kWp-1 and 1,196 kWh kWp-1, while the PRmea for the system ranges from 0.729 to 0.762. This research presents actual data to support the conclusion that the system is underperforming, resulting in a dissatisfied system owner since the PRmea for 2019 and 2020 falls short of the GCPV PR requirement as announced by Sustainable Energy Development Authority (SEDA) Malaysia.